Salud bucal y estilos de vida en adolescentes con adicción al consumo de alcohol - Carrión Moreno, Evelyn Maricela (2023)
ABSTRACT: Harmful alcohol consumption and dependence in adolescents is considered an important public health, social and economic problem, being related as a risk factor for more than 200 health problems, the World Health Organization (WHO) in 2021, starts a campaign called SAFER "live better, drink less", together with a digital health worker, which will support governments and individuals to reduce alcohol consumption. The present research aimed to analyze oral health and lifestyles in adolescents with alcohol addiction. The study is descriptive, cross-sectional and documentary based on articles published in the last 10 years, using databases such as PubMed, Medighapich, Scielo, Research gate, Elservier. Sixty-seven articles were obtained for the systematic review and were submitted to evaluation instruments. After the analysis of the articles, it was found that the most frequent lifestyles in alcohol addiction were inadequate diet, bad oral habits, carelessness, lack of physical activity and cigarette smoking. Oral effects of alcoholism were identified as caries, periodontal disease, dental wear, xerostomia, mucosal changes and cancer. It is suggested that in the dental office, prevention plans or information points about the subject should be implemented in order to have a healthier and more optimal lifestyle control. Key words: alcoholism, oral health, lifestyles, addiction.